Mapping The Landscape of Fraudulent Financial Statement Research: A Systematic Literature Review and Bibliometric Analysis - Elsa Sari Yuliana (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study systematically maps the development of research on fraudulent financial statements and identifies future research directions through a combined systematic literature review and bibliometric analysis. Using the Scopus database, 432 documents published between 1999 and November 16, 2025 were initially identified, and after applying predefined inclusion and exclusion criteria, 88 journal articles were retained for in-depth analysis. Bibliometric techniques supported by VOSviewer were employed to examine publication trends, country and institutional contributions, core journals, influential authors, and frequently co-occurring keywords, thereby revealing the intellectual structure of this research domain. The findings show that scholarly attention to fraudulent financial statements has grown significantly in the last decade, with Indonesia emerging as the most productive country, followed by the United States and several other developed and emerging economies. Conceptually, the literature converges on four main indicator groups—financial ratios, corporate governance mechanisms, behavioral indicators, and technological developments—while commonly used proxies include profitability, leverage, growth measures, audit and governance characteristics, executive behavior, and industry factors. This review highlights that research remains concentrated in developing countries and calls for broader evidence from developed markets, stronger integration of advanced analytics such as artificial intelligence and natural language processing, and more interdisciplinary approaches that link accounting, criminology, and behavioral perspectives. The study provides an evidence-based agenda for future research and offers practical insights for auditors, regulators, and corporate decision-makers seeking to enhance the detection and prevention of fraudulent financial reporting.